Elevational Gradients as a Model for Understanding Associations Among Temperature, Breeding Phenology and Success - Bründl, Aisha C.; Sallé, Louis; Lejeune, Léa A.; Sorato, Enrico; Thiney, Alice C.; Chaine, Alexis S.; Russell, Andrew F. (Frontiers in Ecology and Evolution, 2020)
Climate change is associated with advancing phenology of seasonal traits in many taxa, but shifts by higher trophic levels are generally reduced compared with those of lower trophic levels. For example, the eclosion date of caterpillars and the lay date of insectivorous passerine birds have both advanced recently, but the former has done so more than the latter. While the ensuring phenological mismatch between predator and prey is well-documented, our understanding of the origins of this mismatch is more limited. Here we shed light on the interplay between ambient temperature, breeding phenology and reproductive success in a single population of blue tits (Cyanistes caeruleus) nesting over a 1000 m ( 5 °C) elevational gradient in the French Pyrenees. During the six years of this study, we found that average breeding phenology varied by 2-9 days among years, but was on average 11 d earlier at low versus high elevation. Despite the delay, breeding at high elevation was associated with lower and more variable temperatures during breeding. Early breeders within a given year generally had larger clutch sizes than late breeders, which led to more offspring fledged as typically found in other studies. However, in three of the six years, the probability of producing fledglings was actually lower among early layers. Additionally, birds breeding at high elevations who experience conditions typical of early breeders in other populations had reduced hatching success and were significantly less likely to fledge any young compared with those breeding at lower elevation. Reduced success at high elevation was not obviously driven by higher nest predation, which was exceptionally low, or reduced food availability because high elevation birds laid clutches of comparable size and fledged the same number of offspring of comparable mass as those breeding at low elevation. Our study reveals the capacity for substantial variation in breeding phenology within a population, but that the success of early breeders varies across years and temperature gradients. We suggest that the evolution of phenological advancements by small endotherms might be curtailed by increased probability of experiencing, and failure under, challenging meteorological conditions in late winter or very early spring.